SUB-REGIONAL DESCRIPTIONS OF GLOBAL GPS VECTOR FIELD AND ITS GEODYNAMIC SIGNIFICANCE - Ma Z.; Zhang J.; Ren J.; Li Z. (My University, 2006)
Based on the global vector field of plate movement shown by GPS stations chosen averagely, some characteristics of present plate tectonics can be distinguished as follows: (1) from the northern Atlantic ridge to the island arcs of the northwestern Pacific, the Eurasian Plate broadly shows a clockwise arc-shaped movement; (2) the North American Plate rotated counter-clockwisely, showing are-shaped movement; (3) from the eastern part of the southern Atlantic ridge to the Kemadec - New Zealand Arc, the movement of the African Plate and Indian - Australian Plate change from NE to NNE gradually; (4) the Pacific Plate to the west of the southeastern Pacific Rise broadly moves to the WNW; (5) several small plates to the east of the southeastern Pacific Rise move to the ENE; (6) the South American Plate moves to the north as a whole; (7) the Arctic region moves to the east as a whole; and the Antarctic region moves to the Atlantic Ocean region in general, which also shows the evidence of rifting and rotation. By analyzing the above characteristics of movements of plates globally, we can deduce the following understandings on the kinematics and dynamics of plate tectonics: (1) the mantle flows which result in the movement of plates at the global scale can be divided into sub-flows in the directions of the longitude and latitude, which lead to the oblique movement of many plates; (2) the outer shell of the Earth with characteristics of the double-asymmetry of the Earth shown by lower order geoid is the mechanical precondition to the developments of the oceanic ridges and subduction zones; (3) the complicated phenomena of transpression and transtention along the equatorial disharmony zone maybe result from the velocity difference of rotation between the Southern Hemisphere and the Northern Hemisphere and non-superposition of the centroid of the Earth with its geometrical center; (4) further study on the movement away from the pole of the Antarctic Plate related to the Peri-Antarctic oceanic ridge is needed. Based on the above phenomena, we discussed the causes resulting in the distribution of the three main oceanic ridges on the outer shell of the Earth, development of deep subduction zones only along the Peri-Pacific Ocean, the differences of the longitudinal and latitudinal movements of plates between the Northern Hemisphere and Southern Hemisphere. The reasons for these are related to the double-asymmetry of the Earth as a whole, namely, the double-asymmetry of shrinking and swelling, and slow and rapid rotation between the Northern Hemisphere and Southern Hemisphere and between 0° Hemisphere and 180° Hemisphere The double-asymmetry results from the distribution of mass, movement and thermal statuses of the interior of the Earth. We think that the outer shell of the Earth with the characteristics of double-asymmetry shown by the lower order geoid of the Earth is not only the upper boundary condition for restricting the mantle flows, but also the mechanic precondition leading to the development of the rifting zones on the outer shell of the Earth. The present tectonic units of global scale on the surface of the Earth have not occurred randomly, which are controlled by profound geophysical settings. So, we conjecture that geophysical settings different from those of the present Earth controlled the plate tectonics before the Cenozoic. Based on this supposition we can roughly depict the geophysical setting controlling the plate tectonics of that time. In this paper the mechanic setting resulting in the double-asymmetry of the Earth is discussed. And on the basis of the GPS data, the framework of the combined longitudinal and latitudinal flows of global scale driving by thermal evolution of the Earth was set up and was also discussed.
Keywords: CENTROID; COMBINED LONGITUDINAL AND LATITUDINAL MANTLE FLOW; DIFFERENCE OF ROTATION; DOUBLE-ASYMMETRY OF THE EARTH; GPS VECTOR FIELD; LOWER ORDER GEOID OF THE EARTH; THE EQUATORIAL DISHARMONY ZONE